Economic Improvement of Small and Medium Business through the Utilization of Waste - Rahmawati Rahmawati; Ubaidillah Ubaidillah; Dwi Prasetyani; Ratna Endah Santoso; Rum Handayani; Siti Nurlela (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
This research aims to downstream/commercialize integrating the management of export-scale wood products with the potential for waste wood chips and sawdust as an impact, so as to increase village potential and create an environmentally friendly village in Manggung village in order to increase village potential. This research was conducted as a leap in the field ofwood product management and processing of waste wood scraps and sawdust into handicrafts and accessories. Improved financial management and marketing of wood production in Manggung village through improving the quality of human resources as well as export-import training to help increase exports of wood products as well as handicrafts and accessories. By utilizing local potential and local wisdom and increasing the role of persons with disabilities and victims of layoffs through training to increase knowledge and skills by cooperating with the support of the Boyolali District Government. Institutional strengthening of BUMDes Maju Makmur in optimizing the management of wood and wood waste through mentoring, training and provision of supporting equipment as well as improving governance capabilities and establishing teaching factories that will be used to study undergraduate students.